Brain representation of action observation in human infants. (April 2015) - Burzi, Valentina; Marchi, Viviana; Boyd, Roslyn N; Mazziotti, Raffaele; Moscarelli, Michele; Sgherri, Giada; Tealdi, Gessica; Cioni, Giovanni; Guzzetta, Andrea
Abstract : Imitative learning has long been established as extremely important for early development. However, neural mechanisms involved in early imitative behaviours are still areas of active research. Neurophysiological and brain‐imaging studies have been recently performed that provide initial evidence of brain activation associated with action observation in the first months of life. In this review we examine all studies exploring the effects of action observation on brain function assessed by means of non‐invasive brain‐mapping techniques. Seventeen papers were selected as a result of our literature search. The strongest evidence for a neural signature of action observation comes from studies exploring the desynchronization of the μ ‐rhythm, which was reported for both occluded and visible goal‐directed grasp, and was correlated with the totality of the infant's own action experience. The effects of action observation were reported on event‐related potentials (ERPs) or near infrared spectroscopy. Taken together, these studies suggest that, in early infancy, a direct visual–motor matching process is already detectable as early as 6 months, suggesting a matching between action perception and execution already in infancy. If confirmed by future studies, these findings will shed light on the mechanisms of early motor development and imitation, and will be key to informing novel rehabilitation strategies in infants with congenital brain damage. What this paper adds: A direct visual–motor matching process involved in action observation is detectable from early infancy. Neural correlates of action observation involve a network centred on central, frontal, and parietal nodes. Experience has a key role in modelling the action observation network.